Discrete inverse problems for the Schrödinger operator on the multi-dimensional square lattice with partial Cauchy data. (7th April 2016) - Horváth, Miklós; Markó, Zoltán
Abstract: Motivated by the known results for an ongoing problem, in this paper we define the partial Cauchy data set for the discrete Schrödinger operator on a finite subset of the grid, and we prove a reconstruction theorem for the potential. Our methods are applicable in some general situations; we give a potential reconstruction theorem in the case of the hexagonal lattice as an example.